Encapsulation of salicylic acid in acylated low molecular weight chitosan for sustained release topical application - Tiew, S.X.; Misran, M. (Wiley, 2017)
Acylated low molecular weight chitosan was used to encapsulate salicylic acid (SA) for sustained release in topical delivery. Chitosan nanoparticles were prepared from the depolymerization of commercial chitosan and further acylated with short alkyl chains. The successful acylation of butyryl chitosan [low molecular weight chitosan (LMWC)-B] were proved by Fourier transform infrared (FTIR) and 1H-NMR. Successful encapsulation of SA was observed by the shift of amide I band from 1648 cm−1 in LMWC-B to 1641–1633 cm−1 in SA-loaded LMWC-B in FTIR analysis, which further confirmed with the size increment from dynamic light scattering and transmission electron microscopy analyses by comparing its unencapsulated LMWC-B. SA release from LMWC-B studied by Franz diffusion experiment followed Korsmeyer–Peppas model where the release component n value (0.502) indicated diffusion and polymer swelling were involved in release mechanism. The slow release study of SA showed the acylated chitosan exhibited sustained release property toward SA.